(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Financial engineering refers to the generation of new instruments or securities to meet the need of investors or refinancing providers for financing instruments, the research aims to highlight the importance of financial products in activating and developing, the stock market as a source of financing for the economy. Where the multiplicity and diversity of financial products traded in the stock market is a cornerstone of its efficiency and development, the diversification of financial products can be used as a hedge against the risk of trading securities. The research was to highlight these risks and how to reduce them, through financial engineering productsmany conclusions and recommendations have been reached.